The supporting role of physical exercise in the prevention end treatment of neurodegenerative and mental diseases - Celestyna GRZYWNIAK (Baltic Journal of Health and Physical Activity)
The aim of the article is to draw attention to the possibility of using physical exercises in treating neurodegenerative diseases such as Parkinson’s, Alzheimer’s, multiple sclerosis, dementia as well as mental disorders, particularly depression. This article emphasizes the significance of physical exercise in stimulating the nervous system, including the glial cells, as well as their role in the production of proteins called myokines and myostatins belonging to cytokines. It briefly characterizes the most common neurotrophins in the human body including the BDNF and their role in stabilizing and treating neurodegenerative and mental diseases. It presents the secretory functions of skeletal muscles, which act as a factory producing active chemical substances. This way skeletal muscles communicate chemically with various organs affecting the physiological state of the liver, fat tissue, intestines, pancreas or the immune system. Working skeletal muscles affect the entire human metabolism. Quoting scientific research, the author indicates that adequately dosed physical activity may be effective in treating various neurological and psychiatric disorders, often as much as pharmaceuticals and in some cases even more. She also emphasizes the type of exercise used in treating mental and neurodegenerative diseases as well as the necessity of adjusting them to the psychophysical capability of the trainees.